Implementation model characters strengthening based on 5s to support the halal industry in Universitas Negeri Yogyakarta and International Islamic University Malaysia - Widodo, Syukri Fathudin Achmad; Nuryanto, Apri; Widarto, Widarto; Sukardi, Sukardi; Kartika, Betania; Harjanto, Chrisna Tri; Prasetya, Tri Adi (Universitas Negeri Yogyakarta, 2023)
This research aims to: (1) Know the process of implementing the 5S character strengthening model; (2) Know the behavior of students in applying the 5S character strengthening model; (3) Know how many students apply the 5S attitude. The method used is quantitative descriptive. Experts validate the instruments that have been developed. The results showed: (1) The process of implementing the 5S-based character strengthening model to support the halal Industry for UNY and IIUM students was carried out for four weeks; (2) More and more UNY and IIUM students are applying 5S-based character behavior; (3) The results of quantitative data show the implementation of strengthening the short character at UNY 66.3% and IIUM 68%, set in Order at UNY 68.8% and IIUM 73.3%, shine at UNY 71% and IIUM 68%, standardize at UNY 70.5% and IIUM 67.1%, sustain at UNY 67.7% and IIUM 68.3%.